Funding the planet’s future - Tim Wall (Africa Renewal, 2015)
The delegates at the Third International Conference on Financing for Development in Addis Ababa will discuss how to finance global sustainable development goals, forecast by the UN Conference on Trade and Development (UNCTAD) to cost 2.5 trillion a year over the next 15 years. The biggest challenge humanity faces today is how to achieve a minimal level of prosperity and well-being while protecting the planet at the same time.